The role of PEG/glycerol ratio on the structure and corrosion protection properties of PU-silica coating - Braz, Álvaro G. [UNESP]; Pinto, João V. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP] (Elsevier, 2024)
In this work, investigation was made of the effect of incorporation of polyethylene glycol (PEG) in glycerol-based PU-silica coatings, with the aim of enhance thermal, mechanical, and corrosion protection properties, and establish a comprehensive knowledge regarding the synthesis of novel hybrid PU coatings with variable PEG/glycerol molar ratio. Nuclear magnetic resonance (13C NMR) and Fourier transform infrared (FTIR) spectroscopy analyses showed the conjugation of the PEG to the PU structure by urethane bonds, with the samples prepared using a higher amount of PEG presenting a less rigid structural conformation. Small-angle X-ray scattering (SAXS) measurements demonstrated a correlation between the inorganic fractal dimensionality and the PEG amount. The increasing PEG content contributes to improve thermal stability, coating roughness, and scratch hardness, that achieves typical values of 230 °C, 115 nm and 6H, respectively. As an anticorrosive barrier for steel, the 1.5 μm thickness coating prepared with 75 % glycerol and 25 % PEG exhibits an impedance modulus exceeding 10 GΩ.cm2 over 28 days in contact with saline solution. This new PEG/glycerol-based PU-silica coating proves highly suitable functional features for anticorrosive applications, offering commendable thermal stability, low thickness, high scratch resistance, and impressive impedance.
Keywords: Coating; Corrosion protection; Polyethylene glycol; PU-silica hybrid; Sol-gel process; Surface hardness